10.3928/02793695-20090201-02 (CrossRef Listing of Deleted DOIs, 2000)
Background Traditional educational methods often require protected time away from clinical duties, can be difficult to attend because of staffing or scheduling constraints, and may not consistently engage learners or meet individual learning needs. This article describes a gamified in situ microlearning approach to nursing professional development within the clinical practice setting that was designed to improve confidence and knowledge retention while maintaining staff satisfaction. Method The educational intervention was provided in the clinical setting to avoid scheduling conflicts and interruptions in care. Results Education on 18 topics was provided over 12 months. The gamified microlearning was associated with increased self-reported confidence without negatively impacting satisfaction. Conclusion Gamified in situ microlearning can serve as a valuable adjunct to nursing professional development.